Implementasi Kebijakan Program Indonesia Pintar Jenjang Sekolah Luar Biasa Di Provinsi Sumatera Selatan - Yanti, Yanti; Lisdiana, Lisdiana; Hestirinaih, Deby Chintia (@-Publik: Jurnal Administrasi Publik, 2025)
The Smart Indonesia Program (PIP) is a government assistance program in the form of cash directly provided to students according to established criteria. This program aims to equalize educational opportunities and improve educational quality. It also aims to reduce dropout rates and provide greater attention to the poor. Applicants for the PIP program must be registered in the government’s social welfare database known as DTKS (Integrated Social Welfare Data), have complete educational records, and be listed in the KKS (Prosperous Family Card) system.. The purpose of this study was to determine and analyze the implementation of the Smart Indonesia Program policy for special schools in South Sumatra Province. Problems identified include: many students categorized as poor and vulnerable to poverty do not receive funding from the Smart Indonesia Program; the amount of PIP assistance received by students is perceived as insufficient for school needs; and disbursement of assistance sometimes does not meet the stipulated timeframe. The study found that the criteria for PIP assistance recipients in special schools in South Sumatra Province are in accordance with regulations, as those receiving assistance are registered as poor households and registered in the Integrated Social Welfare Data (DTKS) of Palembang City. The distribution of aid is in accordance with applicable policies, but the amount of aid is deemed insufficient to meet all students' needs.